Effectiveness of Green Feed and Tofu Dregs Mixture on Rectal Temperature, Heart Rate and Respiratory Frequency of Sheep - Sari, Wenny N.; Syakir, Ahmad; Kamal, Mustafa; Wahyudi, Reza; Mustaqim, Mustaqim (Syiah Kuala University, 2025)
Sheep feed sources can be provided in the form of forage and tofu dregs, and the most important thing is feed that meets the needs of protein, carbohydrates, fat, and vitamins and minerals. This study aims to determine the effect of feeding between forage and tofu dregs on rectal temperature, respiratory rate and heart rate. This study was conducted from October to November 2024. The design used in this study was a Randomized Block Design (RAK) with 4 treatments and 3 replications. The results of the study can be concluded that the effect of providing different forage and tofu dregs showed no significant difference (P 0.05) on rectal temperature, heart rate and respiratory rate of sheep. The highest average rectal temperature was seen in treatment D, which was 37.740C and the lowest average was in treatment B, which was 37.640C. The highest average heart rate was seen in treatment D, which was 64.84 times/minute and the lowest average was in treatment B, which was 58.04 times/minute. The highest average respiratory frequency was seen in treatment D, namely 71.93 times/minute and the lowest average was seen in treatment A, namely 66.49 times/minute.